Key technologies and introduction strategies for 3GPP R16 oriented evolution of 5G core network - Xu YANG; Ziyu XIAO; Ming ZHANG; Yongping SHAO (Dianxin kexue)
5G core network has been deployed based on 3GPP R15 standard.Firstly, the progress of 3GPP standard and the overall progress of end-to-end industry of 5G core network were reviewed, and the main research directions and contents of R16 based on the evolution of 3GPP R16 standard were summarized, Then, the key technology research and deployment strategy analysis were carried out for some key issues with relatively high priority in the follow-up business.Finally, the overall summary and analysis of the follow-up 5G core network business evolution deployment direction were carried out, and the preliminary deployment strategy suggestions were put forward, so as to provide reference for the follow-up business evolution and construction of 5G SA core network.